2018
DOI: 10.1038/pr.2017.309
|View full text |Cite
|
Sign up to set email alerts
|

RSV vs. rhinovirus bronchiolitis: difference in nasal airway microRNA profiles and NFκB signaling

Abstract: BackgroundAlthough rhinovirus infection is associated with increased risks of acute and chronic respiratory outcomes during childhood compared with respiratory syncytial virus (RSV), the underlying mechanisms remain unclear. We aimed to determine the differences in nasal airway microRNA profiles and their downstream effects between infants with rhinovirus and RSV bronchiolitis.MethodsAs part of a multicenter cohort study of infants hospitalized for bronchiolitis, we examined nasal samples obtained from 16 infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 44 publications
5
41
1
Order By: Relevance
“…However, several recent studies demonstrate the heterogeneity of bronchiolitis by infecting virus. For example, research has shown that RSV and RV infection are associated with differential acute (eg, disease severity) 5 and chronic (eg, incident asthma) 6,7 morbidity burdens, host response (through transcriptomics, 8,9 cytokines, 10 and metabolomics 11,12 ), and airway microbiome profiles 9,13,14 . Despite the clinical and research relevance, it remains unclear how different viruses (including RV species) systemically contribute to downstream molecules that influence clinical outcomes in infants with bronchiolitis.…”
Section: Introductionmentioning
confidence: 99%
“…However, several recent studies demonstrate the heterogeneity of bronchiolitis by infecting virus. For example, research has shown that RSV and RV infection are associated with differential acute (eg, disease severity) 5 and chronic (eg, incident asthma) 6,7 morbidity burdens, host response (through transcriptomics, 8,9 cytokines, 10 and metabolomics 11,12 ), and airway microbiome profiles 9,13,14 . Despite the clinical and research relevance, it remains unclear how different viruses (including RV species) systemically contribute to downstream molecules that influence clinical outcomes in infants with bronchiolitis.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the high IFN‐levels in the RSV‐positive group may also be due to the presence of extrinsic regulatory factors present in the mucosa of the respiratory tract of infants. For instance, previous studies have shown that the cytokine profile, host transcriptome, microRNAs and the microbiota composition of the airways of infants are quite different during RSV infection relative to other viruses 45,46 . Given the new evidence presented in our study that IFN‐lambda production in human infant AECs can be regulated by pro‐inflammatory signals (eg, IL1β), it is possible that the high levels of IFN lambda during RSV infection are a secondary effect arising from primary dissimilarities in the immune responses against RSV relative to other viruses.…”
Section: Discussionmentioning
confidence: 72%
“…Conversely, miR-22 was shown to be suppressed in asthmatic epithelium in IFV infection which lead to aberrant epithelial response, contributing to exacerbations (Moheimani et al, 2018). Other than these direct evidence of miRNA changes in contributing to exacerbations, an increased number of miRNAs and other non-coding RNAs responsible for immune modulation are found to be altered following viral infections (Globinska et al, 2014;Feng et al, 2018;Hasegawa et al, 2018). Hence non-coding RNAs also presents as targets to modulate viral induced airway changes as a means of managing exacerbation of chronic airway inflammatory diseases.…”
Section: Mirna and Other Epigenetic Modulation Of Inflammationmentioning
confidence: 99%